Utilization of chicken eggshell in body scrub formula with rosella extract (Hibiscus sabdariffa Linn) to improve skin moisture - Nafiah, Rahma; Nurohman, Ikra; Shofa, Dara Kamelia (Universitas Ahmad Dahlan, 2025)
Chicken eggshells contain calcium carbonate, which can function as an exfoliating agent for dead skin cells in the epidermis. Rosella flower contains anthocyanins, which maintain skin moisture through their antioxidant activity. This study aimed to create a body scrub formula combining chicken eggshell and rosella extract, which provides a moisturizing effect on the skin. The study began with the preparation of chicken eggshell powder and rosella flower extract. The body scrub formulation combines eggshell powder and rosella extract with different concentration variations: F1 10%:0.5%, F2 10%:1.0%, and F3 10%:1.5%. The formula was evaluated and characterized using Fourier Transform Infrared (FTIR) spectroscopy, and freeze-thaw stability test were carried out. Irritation test was conducted on rabbits. The occlusive test was conducted in vitro using filter membranes, and a moisture test was performed on 15 volunteers over 28 days using a skin analyzer. The evaluation results show that the formula is cream-colored, homogeneous, semi-solid, with a pH of 6 and a spreadability of 4 cm. Stability tests result showed that the formula was stable in terms of organoleptic properties, although a pH increase was observed. FTIR characterization showed no new interactions formed in the formula. The irritation test showed that the formula does not cause irritation. The occlusive test indicates that the formula retains water vapor for up to 48 hours. The moisture test results show that the formula can moisturize the skin by 60% on the 16th day, with the Mann-Whitney test yielding a p-value of 0.728 for F2 compared to the control. Based on these results, it can be concluded that the body scrub formula combining chicken eggshells and rosella extract effectively moisturizes the skin and does not cause irritation.